Fuzzy-Based Extraction of Vascular Structures from Time-of-Flight MR Images - Forkert, Nils Daniel; Säring, Dennis; Karolin Wenzel; Illies, Till; Fiehler, Jens; Heinz Handels (Studies in health technology and informatics, 2009)
In this paper an automatic fuzzy based method for the extraction of the cerebrovascular system from 3D Time-of-Flight (TOF) MRA image sequences is presented. In order to exclude non-brain tissue an automatic skull stripping method is applied in a preprocessing step. Based on the TOF images vesselness and maximum parameter images are computed first. These parameter images are then combined with the TOF sequence using a fuzzy inference. The resulting fuzzy image offers an improved enhancement of small as well as malformed vessels against the remaining brain. Finally, the fuzzy-connectedness approach is used to extract the vascular system. A first evaluation showed that the fuzzy-based method proposed performs better than a state of the art method and yields results in the range of the inter-observer variation.
Keywords: Blood Vessels; Fuzzy Logic; Humans; Imaging, Three-Dimensional; Magnetic Resonance Imaging; Stroke